HUNIAN VERTIKAL EKOLOGIS TERJANGKAU DI MANGGARAI: SOLUSI KOTA PADAT YANG BERKELANJUTAN - Ferdinand, Priscillia Angel Ruth Meyoki; Gandha, Maria Veronica (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Land use in Jakarta has undergone significant transformation due to rapid population growth and urbanization. One of the most extensive land conversions has occurred in green open spaces, which have been turned into residential and commercial areas. As a result, Jakarta faces a range of problems, including reduced water catchment areas, traffic congestion, and environmental degradation caused by biodiversity loss and rising carbon emissions. The Biodiverse Habitat concept is proposed as a regenerative strategy in response to ecological degradation and urban density. It adopts the principles of Transit-Oriented Development (TOD), with a focus on integrating green spaces, promoting ecological sustainability, and optimizing land use within a unified system, which is also designed to provide affordable housing in strategic locations with access to public transit. Many affordable housing options in Jakarta are located far from public transportation access, leading to mobility inequality and a lower quality of life for low-income communities. Through vertical zoning, the design combines ecological and residential functions within the same site. Green open spaces and water catchment areas are placed at ground level, serving as urban parks, public spaces, and habitats for local flora and fauna. Above these, vertical housing and commercial areas are constructed to accommodate dense urban living more efficiently. By placing affordable housing within walkable distance to major transit hubs, the concept promotes more equitable accessibility and reduces reliance on private vehicles. This concept also applies principles of ecological architecture through natural rainwater absorption systems and the use of renewable energy. Implementing the Biodiverse Habitat offers Jakarta the opportunity to move toward more sustainable urban development. In addition to improving residents' quality of life, this approach restores the ecological function of land and supports environmental balance within the dense urban landscape. Manggarai has been selected as the project site due to its characteristics as one of Jakarta’s most densely populated areas, its strategic location, and the presence of major transportation hubs such as train and bus stations—making it highly suitable for TOD-based development. The existing conditions, marked by limited green space and declining function, further emphasize Manggarai’s relevance for an intervention that integrates housing, ecology, and mobility within a cohesive design strategy. Keywords: affordable; ecology;  housing;  vertical Abstrak Fungsi lahan di Jakarta mengalami transformasi yang signifikan akibat pertumbuhan populasi dan urbanisasi yang pesat. Salah satu bentuk konversi besar-besaran terjadi pada ruang terbuka hijau yang beralih menjadi kawasan permukiman dan komersial. Akibatnya, Jakarta menghadapi berbagai permasalahan, termasuk berkurangnya area resapan air, kemacetan lalu lintas, serta penurunan kualitas lingkungan akibat hilangnya biodiversitas dan meningkatnya emisi karbon. Konsep Biodiverse Habitat diajukan sebagai strategi regeneratif untuk merespons degradasi ekologis dan tingginya kepadatan kota. Konsep ini mengangkat prinsip Transit-Oriented Development (TOD) dengan penekanan pada integrasi ruang hijau, keberlanjutan ekologi, dan optimalisasi fungsi lahan dalam satu sistem terpadu yang juga dirancang untuk menghadirkan hunian terjangkau di lokasi strategis berbasis transportasi publik. Hunian terjangkau yang tersedia di Jakarta tidak memiliki akses langsung dengan transportasi publik, sehingga menimbulkan ketimpangan dalam mobilitas dan kualitas hidup masyarakat.  Pendekatan desain dilakukan dengan mengombinasikan fungsi ekologis dan fungsi hunian pada satu area lahan melalui sistem zonasi vertikal. Ruang terbuka hijau dan kawasan resapan air dirancang berada di lantai dasar sebagai taman kota, ruang publik, serta habitat bagi flora dan fauna lokal. Sementara itu, hunian vertikal dan area komersial dibangun di lapisan atasnya untuk menjawab kebutuhan hunian padat secara efisien. Hadirnya hunian terjangkau dalam jarak tempuh berjalan kaki menuju moda transportasi, konsep ini mendorong aksesibilitas yang lebih merata dan mengurangi ketergantungan pada kendaraan pribadi. Konsep ini juga menerapkan prinsip ecology architecture melalui sistem penyerapan air hujan alami dan pemanfaatan energi terbarukan. Selain meningkatkan kualitas hidup masyarakat, pendekatan ini juga mengembalikan fungsi ekologis lahan serta menciptakan keseimbangan lingkungan di tengah lanskap urban yang padat. Kawasan Manggarai dipilih sebagai lokasi penerapan karena memiliki karakteristik sebagai salah satu wilayah dengan kepadatan penduduk tinggi, lokasi strategis, serta keberadaan simpul transportasi utama seperti stasiun dan halte yang menjadikannya sangat potensial untuk pengembangan berbasis TOD. Kondisi eksisting yang mengalami penurunan fungsi dan minim ruang hijau juga menjadikan Manggarai relevan untuk intervensi konsep yang menggabungkan hunian yang efisien, ekologis, dengan mobilitas tinggi.